Media sosial sebagai alat penguat identitas nasional di Indonesia - Shakila, Aqilah Rafa (Maliki Interdisciplinary Journal, 2025)
The rapid development of information technology has made social media an important part of people's lives, especially the millennial generation. This study aims to analyze the role of social media in strengthening national identity among the younger generation of Indonesia. The method used is a literature study with a literature study approach. The results of the discussion show that social media can be an effective means of spreading Indonesian cultural, historical, and traditional values. In addition, this platform also facilitates intergenerational and intercultural dialogue that encourages social solidarity and a sense of national pride. However, if not used wisely, social media can also trigger polarization and disinformation. Therefore, strong digital literacy is needed so that social media can be utilized optimally in forming a national identity.